The Physycal Nature of the Optical Emission and Absorption Accompanying Explosive Decomposition of Heavy Metal Azides - Oleshko V. I.; Korepanov V. I. Vladimir Ivanovich; Lisitsyn V. M. Viktor Mikhailovich; Tsypilev V. P. (2004, 2004)
В фонде НТБ ТПУ отсутствует